2021
DOI: 10.3390/agronomy11020214
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Development and Productivity in Response to Organic Management above the Northern Boundary of Soybean Distribution in Europe

Abstract: Climate change, new varieties, better technological abilities, and increased demand for local resources provide significant reasons to introduce soybeans in northern regions, above the typical soybean distribution area in Europe. This research examined the effects of two delayed sowing times, wide 25 cm and 50 cm row spacings, seed inoculation with Bradyrhizobium japonicum, and the interaction of all these factors on soybean development and productivity in an organic farming system. Length of soybean vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The effect of year, cultivar, and tillage on 1000-grain weight (g) A significant yield component is 1000-grain weight, which besides yield, serves as the best indicator of suitability for soybean production across years or regions (Dozet et al, 2009). The results obtained by Toleikiene et al, (2021) indicated that unfavourable growing conditions during seed reproductive growth stage significantly affected 1000-grain weight. Soybean cultivars Rubin and Sava had the highest 1000-grain weight, whereas Galina had the lowest value for the trait, both after autumn and spring primary tillage (Table 5).…”
Section: Resultsmentioning
confidence: 94%
“…The effect of year, cultivar, and tillage on 1000-grain weight (g) A significant yield component is 1000-grain weight, which besides yield, serves as the best indicator of suitability for soybean production across years or regions (Dozet et al, 2009). The results obtained by Toleikiene et al, (2021) indicated that unfavourable growing conditions during seed reproductive growth stage significantly affected 1000-grain weight. Soybean cultivars Rubin and Sava had the highest 1000-grain weight, whereas Galina had the lowest value for the trait, both after autumn and spring primary tillage (Table 5).…”
Section: Resultsmentioning
confidence: 94%
“…Najveća masa 1.000 zrna bila je u najpovoljnijoj proizvodnoj 2014. godini (189,99 g), za razliku od druge dve godine. Istraživanje Toleikiene et al (2021) ukazuje da su nepovoljni uslovi tokom faze reproduktivnog rasta značajno uticali na smanjenje mase 1.000 zrna. Stimulacija semena sa PEMP je pozitivno uticala na povećanje mase 1.000 zrna (155,87 g) u odnosu na varijantu bez stimulacije (152,83) na nivou značajnosti od p<0,01.…”
Section: Rezultati I Diskusijaunclassified
“…However, during the last decade its growing area has expanded towards the north, due to climate change as well as plant breeding efforts. Therefore, soybean introduction has entered the applied research agenda in the North Europe region, aimed at expanding the boundary of its cultivation area in Europe [10].…”
Section: Introductionmentioning
confidence: 99%